2015
DOI: 10.1016/j.vaccine.2015.02.074
|View full text |Cite
|
Sign up to set email alerts
|

A microneedle patch containing measles vaccine is immunogenic in non-human primates

Abstract: Very high vaccination coverage is required to eliminate measles, but achieving high coverage can be constrained by the logistical challenges associated with subcutaneous injection. To simplify logistics of vaccine delivery, a patch containing micron-scale polymeric needles was formulated to encapsulate the standard dose of measles vaccine (1000 TCID50) and the immunogenicity of the microneedle patch was compared with subcutaneous injection in rhesus macaques. The microneedle patch was administered without reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 38 publications
3
112
0
1
Order By: Relevance
“…Effective cross-talk between innate and adaptive immune responses generates more robust, longer-lasting immune protection [20,21]. We and other investigators have previously reported that skin immunization with metal or dissolving microneedle patches (MNPs) carrying various vaccines (influenza, inactivated poliovirus (IPV), measles, tetanus, HPV, rotavirus, BCG, malaria and RSV) confers immune responses at least non-inferior to conventional immunization as shown by lethal challenge studies, longevity of immune responses and breadth of immunity in a number of small-animal models [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Effective cross-talk between innate and adaptive immune responses generates more robust, longer-lasting immune protection [20,21]. We and other investigators have previously reported that skin immunization with metal or dissolving microneedle patches (MNPs) carrying various vaccines (influenza, inactivated poliovirus (IPV), measles, tetanus, HPV, rotavirus, BCG, malaria and RSV) confers immune responses at least non-inferior to conventional immunization as shown by lethal challenge studies, longevity of immune responses and breadth of immunity in a number of small-animal models [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This delivery method induced strong cellular and humoral adenovirus-specific vaccination in macaques equivalent to the traditional intramuscular injection [102]. In a recent study, an MN patch containing sucrose and CMC was formulated to encapsulate the standard dose of measles vaccine and was tested in rhesus macaques [103]. The researchers demonstrated that the macaques responded to MN vaccination with equivalent neutralizing antibody titers compared to the conventional subcutaneous injection.…”
Section: Types Of Delivered Proteinmentioning
confidence: 99%
“…115,116 However, unlike hollow MN, a limitation is placed on the amount of vaccine that can be incorporated into the system 117 and vaccinees may be obliged to wait for extended periods of time to ensure complete MN degradation. 114 104 and polio 105 in rhesus macaques, with a long term aim to create a thermostable, selfadministration platform. Although an attractive platform, dissolvable microneedle (DMN) systems for vaccine delivery have required more time to reach clinical trials compared to hollow or solid microneedles.…”
Section: Dissolving Microneedlesmentioning
confidence: 99%